2019
DOI: 10.1186/s12881-019-0915-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel EIF2AK4 mutations in histologically proven pulmonary capillary hemangiomatosis and hereditary pulmonary arterial hypertension

Abstract: BackgroundPulmonary hypertension (PH) remains one of the rarest and deadliest diseases. Pulmonary Capillary Hemangiomatosis (PCH) is one of the sub-classes of PH. It was identified using histological and molecular tools and is characterized by the proliferation of capillaries into the alveolar septae. Mutations in the gene encoding the eukaryotic translation initiation factor 2 alpha kinase 4 (EIF2AK4) have recently been linked to this particular subgroup of PH.MethodsIn our effort to unveil the genetic basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Mutations in EIF2AK4 , the gene that encodes GCN2, are associated with different forms of pulmonary hypertension including pulmonary veno‐occlusive disease, pulmonary capillary hemangiomatosis, and pulmonary arterial hypertension (Abou Hassan et al, 2019; Best et al, 2014, 2017; Eichstaedt et al, 2016; Eyries et al, 2014; Hadinnapola et al, 2017; Table 5). The primary symptoms of pulmonary hypertension are progressive exercise dyspnea, dyspnea on bending down, exercise‐induced syncope, fatigue, and edema (Hoeper et al, 2017).…”
Section: Genetic Diseases Of the Integrated Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in EIF2AK4 , the gene that encodes GCN2, are associated with different forms of pulmonary hypertension including pulmonary veno‐occlusive disease, pulmonary capillary hemangiomatosis, and pulmonary arterial hypertension (Abou Hassan et al, 2019; Best et al, 2014, 2017; Eichstaedt et al, 2016; Eyries et al, 2014; Hadinnapola et al, 2017; Table 5). The primary symptoms of pulmonary hypertension are progressive exercise dyspnea, dyspnea on bending down, exercise‐induced syncope, fatigue, and edema (Hoeper et al, 2017).…”
Section: Genetic Diseases Of the Integrated Stress Responsementioning
confidence: 99%
“…The homozygous or heterozygous compound mutations identified were autosomal recessive (Best et al, 2014). More recently, mutations in EIF2AK4 have been linked to pulmonary arterial hypertension, albeit less commonly (Abou Hassan et al, 2019; Best et al, 2017; Eichstaedt et al, 2016; Hadinnapola et al, 2017). Pulmonary hypertension‐associated EIF2AK4 mutations are thought to be loss of function and likely prevent sufficient ISR activation (Figure 6a,c).…”
Section: Genetic Diseases Of the Integrated Stress Responsementioning
confidence: 99%
“…However, these mutations are variably penetrant, suggesting that additional modifying factors exist. Two subtypes of PAH, pulmonary veno-occlusive disease (PVOD) and pulmonary capillary haemangiomatosis (PCH) were recently shown to be caused by biallelic mutations of EIF2AK4, which encodes GCN2 (figure 3) [163][164][165]. The PVOD/PCH subtypes have an even worse prognosis than classical PAH and currently have no effective treatments apart from lung transplantation [166].…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…However, these mutations are variably penetrant, suggesting that additional modifying factors exist. Two subtypes of PAH, pulmonary veno-occlusive disease (PVOD) and pulmonary capillary haemangiomatosis (PCH) were recently shown to be caused by biallelic mutations of EIF2AK4 , which encodes GCN2 ( figure 3 ) [ 163 165 ].…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…[32][33][34][35] However, emerging evidence has demonstrated that genetic defects play a pivotal role in the pathogenesis of idiopathic PAH, especially for familial PAH, and deleterious mutations in multiple genes, including BMPR2 encoding a receptor of the transforming growth factor-β superfamily, TBX4 encoding a transcription factor, and KCNK3 as well as ABCC8 encoding potassium channels, have been found to cause PAH. 1,4,[36][37][38][39][40][41][42][43][44][45][46][47] In addition, genome-wide association studies have revealed that common genetic variations are associated with an enhanced susceptibility to PAH. 48) Nevertheless, due to substantial genetic heterogeneity of PAH, the genetic determinants underpinning PAH in the overwhelming majority of patients remain to be identified.…”
mentioning
confidence: 99%